MAKNA KECEMASAN KARIER PADA MAHASISWA TINGKAT AKHIR DI FAKULTAS PSIKOLOGI UNIVERSITAS KRISTEN SATYA WACANA - Emanuella Debby Cassella; Rudangta Arianti Sembiring (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Final-year students face various complex challenges during the transition to the workforce. A lack of work-related skills, academic pressures, and uncertainty about the job market can trigger career anxiety that potentially affects their psychological well-being. This study aims to explore the meaning of career anxiety experienced by final-year students at the Faculty of Psychology, Satya Wacana Christian University, as well as the strategies they employ to cope with it. The research employs a qualitative method with a phenomenological approach. The research participants were selected using purposive sampling, and data were collected through semi-structured interviews, observation, and documentation. The data were then analyzed using the Miles and Huberman model. The findings indicate that career anxiety is influenced by four main aspects: individual ability, irrational beliefs about employment, employment environment, and professional education training. The participants expressed concerns about their lack of skills, fear of social judgment, stigma surrounding the psychology profession, and unpreparedness to face professional responsibilities. Nevertheless, both participants demonstrated efforts toward self-development through self-reflection, motivation, and skill enhancement. This study highlights the important role of institutions in providing career support and psychological services. The findings may serve as a reference for designing interventions to help students cope with career anxiety. ABSTRAK Mahasiswa tingkat akhir dihadapkan pada berbagai tantangan kompleks dalam masa transisi menuju dunia kerja. Ketidaksiapan dalam penguasaan keterampilan kerja, beban akademik, serta ketidakpastian terhadap pasar kerja dapat memicu munculnya kecemasan karier yang berpotensi memengaruhi kesejahteraan psikologis. Penelitian ini bertujuan untuk memahami makna kecemasan karier pada mahasiswa tingkat akhir di Fakultas Psikologi Universitas Kristen Satya Wacana serta strategi yang digunakan untuk mengatasinya. Penelitian ini menggunakan metode kualitatif dengan pendekatan fenomenologi. Pemilihan subjek penelitian menggunakan teknik purposive sampling dan data dikumpulkan melalui wawancara semi-terstruktur, observasi dan dokumentasi, kemudian dianalisis menggunakan model Miles dan Huberman. Hasil penelitian menunjukkan bahwa kecemasan karier dipengaruhi oleh empat aspek utama, yaitu kemampuan individu, keyakinan irasional, lingkungan kerja, dan program pelatihan profesional. Partisipan mengungkapkan kekhawatiran akan kurangnya keterampilan, ketakutan akan penilaian sosial, stigma terhadap profesi psikolog, serta ketidaksiapan menghadapi tanggung jawab profesional. Meskipun demikian, partisipan tetap menunjukkan upaya pengembangan diri melalui refleksi diri, motivasi, dan peningkatan keterampilan. Penelitian ini menyoroti pentingnya peran institusi dalam menyediakan dukungan karier dan layanan psikologis. Temuan ini dapat menjadi acuan dalam merancang intervensi untuk membantu mahasiswa menghadapi kecemasan karier.